Penyuluhan Dampak Pernikahan Dini Dan Kesehatan Reproduksi Bagi Anak Remaja Di Kabupaten Mojokerto - Hikmah Muhaimin; Dhiyan Septa Wiharan; Dian Wijaya; Mohammad Resi Abdul Basith (Yayasan Literasi Sains Indonesia, 2022)
The impact of early marriage and reproductive health for adolescents is very influential on all factors, both economic, social, health and educational factors. And early marriage seems to still be happening, including in Indonesia. Especially in Mojokerto Regency, the numbers are very fantastic, the people still do this. Usually the causes of early marriage are cultural and socio-economic factors. Some parents still have the notion that children can be a